Respuesta :

Answer:

A = (12h x b1) + (12h x b2)

A = 12hb1 + 12hb2

A - 12hb1 = 12hb1 - 12hb1 +12hb2

A - 12hb1 = 12hb2

(A - 12hb1) / (12h) = (12hb2) / (12h)

b2 = (A - 12hb1) / (12h)

Answer:

b₂ = [tex]\frac{2A-hb_{1} }{h}[/tex]

Step-by-step explanation:

A = [tex]\frac{1}{2}[/tex] h(b₁ + b₂) ← multiply both sides by 2 to clear the fraction

2A = h(b₁ + b₂) ← distribute

2A = hb₁ + hb₂ ( subtract hb₁ from both sides )

2A - hb₁ = hb₂ ( divide both sides by h )

[tex]\frac{2A-hb_{1} }{h}[/tex] = b₂